Old Drugs with New Tricks: Paradigm in Drug Development Pipeline for Alzheimer’s Disease - Dalvi, Tanay; Dewangan, Bhaskar; Das, Rudradip; Rani, Jyoti; Shinde, Suchita D.; Vhora, Nazmina; Jain, Alok; Sahu, Bichismita (Central Nervous System Agents in Medicinal Chemistry, 2020)
The most common reason behind dementia is Alzheimer’s disease (AD) and it is predicted to be the third life-threatening disease apart from stroke and cancer for the geriatric population. Till now, only four drugs are available on the market for symptomatic relief. The complex nature of disease pathophysiology and lack of concrete evidence of molecular targets are the major hurdles for developing a new drug to treat AD. The rate of attrition of many advanced drugs at clinical stages makes the de novo discovery process very expensive. Alternatively, Drug Repurposing (DR) is an attractive tool to develop drugs for AD in a less tedious and economic way. Therefore, continuous efforts are being made to develop a new drug for AD by repurposing old drugs through screening and data mining. For example, the survey in the drug pipeline for Phase III clinical trials (till February 2019) consists of 27 candidates, and around half of the number are drugs which have already been approved for other indications. Although in the past, the drug repurposing process for AD has been reviewed in the context of disease areas, molecular targets, there is no systematic review of repurposed drugs for AD from the recent drug development pipeline (2019-2020). In this manuscript, we have reviewed the clinical candidates for AD with emphasis on their development history, including molecular targets and the relevance of the target for AD.
Keywords: drug repurposing